Horn Banana Peel Powder Biocoagulants in Lowering the Turbidity of Water - Priyadi , Priyadi; A’yun, Qurrota; Navianti, Diah; Sukarjo , Sukarjo (Penerbit Goodwood, 2024)
Purpose: This study aims to utilize horn banana peel powder, a form of organic waste, as a biocoagulant to reduce water turbidity in dug wells. It addresses the need for environmentally friendly and cost-effective alternatives to chemical coagulants, particularly for households relying on groundwater in rural areas. Research methodology: This research employed a true experimental design using a pre-test and post-test control group. The treatments consisted of biocoagulant doses of 6 g/L, 7 g/L, and 8 g/L. Turbidity was measured using a Hach 2100Q turbidity meter. Data were analyzed using Paired Sample T-Test, ANOVA with Welch correction, and Games-Howell post hoc test to determine statistical significance. Result: The optimal dose of 8 g/L reduced turbidity from 249 NTU to 2.42 NTU, achieving a 99.03% reduction. Statistical analysis (p < 0.05) confirmed significant differences between all treatment groups, validating the biocoagulant’s effectiveness.Conlusions: Horn banana peel powder is an effective, natural alternative to chemical coagulants for improving groundwater quality. It supports circular bioeconomy practices and complies with Indonesian water quality standards.Limitation : The study focused solely on turbidity and did not assess other water quality parameters (e.g., pH, TDS, BOD).Contribution: This research promotes sustainable water treatment solutions using local, biodegradable materials. It demonstrates the potential of fruit waste reuse in environmental health, particularly for clean water access in low-income communities.